Changing adolescence : Social trends and mental health. - Hagell, Ann (Policy Press, 2012)
This unique volume brings together the main findings from the Nuffield Foundation's Changing Adolescence Programme and explores how social change may affect young people's behaviour, mental health and transitions toward adulthood.